Provinciale prijs voor vormgeving 2004. (Gent : Provinciebestuur Oost-Vlaanderen, 2005)
Van der Biest, Francine ; De Pelsmacker, Hans ; Depuydt, Bieke ; De Rudder, Nora ; de Schrevel, Stéphane ; De Baudringhien, Filip ; De Vrieze, Tom ; Dobbelaere, Danny ; Proot, Nick ; Vandekerckhove, Roos